Melanoides tuberculata (Mollusca: Thiaridae) as an intermediate host of Centrocestus formosanus (Trematoda: Heterophyidae) in Brazil - Pinto, Hudson Alves; Melo, Alan Lane de (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
Pleurolophocercous cercariae emerged from naturally infected Melanoides tuberculata from Minas Gerais State, Brazil, were used to perform experimental infection of laboratory-reared Poecilia reticulata. Mature metacercariae were obtained from the gills of fishes and force-fed to Mus musculus. The adult parasites which recovered from small intestines of mice were identified as Centrocestus formosanus. This is the first report of M. tuberculata as intermediate host of this heterophyid in Brazil.